Respuesta :

Answer:

f(x) = (x - 2)² + 2

Step-by-step explanation:

The vertex form of the quadratic function is:

f(x) = a(x - h)² + k

where:

(h, k) = vertex

The axis of symmetry is the imaginary vertical line where x = h

a = determines whether the graph opens up or down, and how wide or narrow the graph will be.

h = determines the horizontal translation of the parabola.

k = determines the vertical translation of the graph.

Given the vertex occurring at point (2, 2), along with one of the points on the graph, (4, 6):

Substitute these values into the vertex form of the quadratic function:

f(x) = a(x - h)² + k

6 = a(4 - 2)² + 2

6 = a(2)² + 2

6 = 4a + 2

Subtract 2 from both sides:

6 - 2 = 4a + 2 - 2

4 = 4a

Divide both sides by 4:

4/4 = 4a/4

1 = a

Therefore, the quadratic function in vertex form is: f(x) = (x - 2)² + 2